2x-6+2x-6+x+3+x+3=26

Simple and best practice solution for 2x-6+2x-6+x+3+x+3=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-6+2x-6+x+3+x+3=26 equation:


Simplifying
2x + -6 + 2x + -6 + x + 3 + x + 3 = 26

Reorder the terms:
-6 + -6 + 3 + 3 + 2x + 2x + x + x = 26

Combine like terms: -6 + -6 = -12
-12 + 3 + 3 + 2x + 2x + x + x = 26

Combine like terms: -12 + 3 = -9
-9 + 3 + 2x + 2x + x + x = 26

Combine like terms: -9 + 3 = -6
-6 + 2x + 2x + x + x = 26

Combine like terms: 2x + 2x = 4x
-6 + 4x + x + x = 26

Combine like terms: 4x + x = 5x
-6 + 5x + x = 26

Combine like terms: 5x + x = 6x
-6 + 6x = 26

Solving
-6 + 6x = 26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 6x = 26 + 6

Combine like terms: -6 + 6 = 0
0 + 6x = 26 + 6
6x = 26 + 6

Combine like terms: 26 + 6 = 32
6x = 32

Divide each side by '6'.
x = 5.333333333

Simplifying
x = 5.333333333

See similar equations:

| 3(-x-3)=4x-2(x+1) | | 25m+.45=40m+.25 | | t-(8*8+0.36)=0.5 | | 3(-x+3)=4x-2(x+1) | | 4t+9=8-13 | | -7.5+5.5(1+9d)=-17.5 | | 15.35+10.25c=353.6 | | 1.4n+4*4*4=85 | | 2m^2-7m+3= | | x^2-2x-240=0 | | 3x-35=128 | | -27.5+4c=-28.5-3y | | 99+x=189 | | 10x+20+12x=180 | | 13x+2=2x+2 | | 5x*8y=12 | | 52-3*7=62 | | 23.99x+120.84x=675.28 | | 3[2p-5]=33 | | 7.5(7y-5)=-28.5-3y | | 8-3a+8a-8b+3b= | | X*45=15 | | x-3+x+8=70 | | -15.5=-6(3.5k+6.5) | | -6w+15=51 | | z^5+2iz^3-4z=0 | | 20.5+3.9t=10.75 | | 10y+5=40 | | 2x+30+3x=180 | | 5a=-11 | | 3y-2=2y-3 | | y=2IN(3x+4) |

Equations solver categories